2006
DOI: 10.1074/mcp.r600008-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in Clinical Trials and Practice

Abstract: The study of clinical proteomics is a promising new field that has the potential to have many applications, including the identification of biomarkers and monitoring of disease, especially in the field of oncology. Expression proteomics evaluates the cellular production of proteins encoded by a particular gene and exploits the differential expression and post-translational modifications of proteins between healthy and diseased states. These biomarkers may be applied towards early diagnosis, prognosis, and pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 60 publications
0
40
0
2
Order By: Relevance
“…Newer semiquantitative and quantitative techniques are being developed to facilitate this important endpoint. 31 The current results indicated that EGFR is present in EOC and is activated in most patients SEM indicates standard error of the mean; EGFR, epidermal growth factor receptor; AKT, protein kinase B; p-ERK, phosphorylated extracellular regulated kinase; GI, gastrointestinal; p-AKT, phosphorylated AKT; pY1148-EGFR, pY1173-EGFR, and pY992-EGFR, phosphorylated forms of epidermal growth factor receptor. * Exact Jonckheere-Terpstra trend test.…”
Section: Discussionmentioning
confidence: 99%
“…Newer semiquantitative and quantitative techniques are being developed to facilitate this important endpoint. 31 The current results indicated that EGFR is present in EOC and is activated in most patients SEM indicates standard error of the mean; EGFR, epidermal growth factor receptor; AKT, protein kinase B; p-ERK, phosphorylated extracellular regulated kinase; GI, gastrointestinal; p-AKT, phosphorylated AKT; pY1148-EGFR, pY1173-EGFR, and pY992-EGFR, phosphorylated forms of epidermal growth factor receptor. * Exact Jonckheere-Terpstra trend test.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, detection of early stage disease offers an opportunity to reduce mortality. Unfortunately, to date, no screening protocol for ovarian cancer has been shown to achieve this aim, and only 19% of ovarian cancer cases are diagnosed at local stage (9,10) Despite advances in molecular biology, surgery, and chemotherapy, survival rates have changed very little in the last three decades. The glycoprotein CA-125 is the most thoroughly investigated biomarker for ovarian cancer screening and is currently the only marker used in combination with transvaginal ultrasound to detect a significant proportion of ovarian cancer (8,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Invariably these RPA studies utilized specific antibodies directed against phosphorylation sites that had been associated with disease before (10). In an RPA format, each position in the array represents a complex protein test sample, such as a serum sample or a tissue lysate, and hundreds of patient samples can be combined on a single array slide.…”
mentioning
confidence: 99%